2019
DOI: 10.21203/rs.2.15773/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-drug resistance of blood stream, urinary tract and surgical site nosocomial infections of Acinetobacter baumannii and Pseudomonas aeruginosa among patients hospitalized at Felegehiwot Referral Hospital, Northwest Ethiopia: A cross-sectional study

Abstract: Background: Multi-drug resistant (MDR) Acinetobacter baumannii and Pseudomonas aeruginosa are major causes of nosocomial infections globally. They are the current World Health Organization critical priority pathogens for resistance, AMR surveillance and discovery of new antibiotics. However, there is paucity of data on nosocomial infections (NIs) caused by such superbugs in Ethiopia. Therefore, this study determined the magnitude and profile of nosocomial MDR Acinetobacter baumannii and Pseudomonas aeruginosa … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 33 publications
2
10
2
Order By: Relevance
“…In this study, the low number of microorganisms produced also significantly affects this results and also we did not plan particularly to assign the risk factors for the acquisition of resistant microbial agents. Conditions such as immunosuppression, use of invasive mechanical ventilation, prolonged length of ICU and hospital stay, poor or restricted respiratory function, patients exposure to high‐risk devices or surgical procedures and prior treatment with broad‐spectrum antibiotics may cause high Acinetobacter baumannii infection rate which is one of the resistant microorganisms 15,16 …”
Section: Di̇scussi̇onmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the low number of microorganisms produced also significantly affects this results and also we did not plan particularly to assign the risk factors for the acquisition of resistant microbial agents. Conditions such as immunosuppression, use of invasive mechanical ventilation, prolonged length of ICU and hospital stay, poor or restricted respiratory function, patients exposure to high‐risk devices or surgical procedures and prior treatment with broad‐spectrum antibiotics may cause high Acinetobacter baumannii infection rate which is one of the resistant microorganisms 15,16 …”
Section: Di̇scussi̇onmentioning
confidence: 99%
“…Conditions such as immunosuppression, use of invasive mechanical ventilation, prolonged length of ICU and hospital stay, poor or restricted respiratory function, patients exposure to high-risk devices or surgical procedures and prior treatment with broad-spectrum antibiotics may cause high Acinetobacter baumannii infection rate which is one of the resistant microorganisms. 15,16 The antimicrobial susceptibility of Acinetobacter species isolated throughout a 10-year in Taiwan was presented and the rate of susceptibility to tigecycline and colistin was 97.7% and 99.8%, and the susceptibility rate of carbapenem-resistant isolates to these drugs was 98.1% and 100%, respectively. 17 An other study showed that the incidence of resistance to imipenem in Acinetobacter baumannii was estimated to 11%.…”
Section: Ta B L E 2 Frequency Of Aetiologic Agents and Administered Antibiotics With Patientsmentioning
confidence: 99%
“…Breast cancer is the second leading cause of death among women all around the world. NIs and cancer lead to increased morbidity, mortality, cost, and hospitalization, as well as inflicting staff and economic pressure to the health centers (Motbainor et al, 2020). The rapid emergence of antibiotic-resistant bacteria has affected the efficacy of infectious disease treatment and the health of millions of patients worldwide (Kajihara et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…e bacterium causes pneumonia, bacteraemia, septicaemia [5], meningitis [6], and urinary tract infections [7] often seen in patients undergoing invasive procedures such as urinary catheter, tracheal intubation, and those with underlying conditions [2]. A. baumannii has demonstrated several antimicrobial resistance mechanisms [8][9][10] against antibiotics such as aminoglycosides, carbapenems, fluoroquinolones, cephalosporins, tetracyclines, sulbactams, rifampicins [9], as well as colistin [11][12][13] and tigecycline [8,14], the so called last resort drugs used to treat its infections [8,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%